Inside charter schools : the paradox of radical decentralization - Fuller, Bruce (Harvard University Press, 2002)
Deepening disaffection with conventional public schools has inspired flight to private schools, home schooling, and new alternatives, such as charter schools. Barely a decade old, the charter school movement has attracted a colorful band of supporters, from presidential candidates, to ethnic activists, to the religious Right. At present there are about 1,700 charter schools, with total enrollment estimated to reach one million early in the century. Yet, until now, little has been known about the inner workings of these small, inventive schools that rely on public money but are largely independent of local school boards. Inside Charter Schools takes readers into six strikingly different schools, from an evangelical home-schooling charter in California to a back-to-basics charter in a black neighborhood in Lansing, Michigan. With a keen eye for human aspirations and dilemmas, the authors provide incisive analysis of the challenges and problems facing this young movement. Do charter schools really spur innovation, or do they simply exacerbate tribal forms of American pluralism? Inside Charter Schools provides shrewd and illuminating studies of the struggles and achievements of these new schools, and offers practical lessons for educators, scholars, policymakers, and parents.